Design and implementation of smart farming prototype with renewable energy and IoT - Susanto, Rudi; Lestari, Wiji; Hasanah, Herliyani (Institute of Advanced Engineering and Science, 2025)
Indonesia faces food security challenges in several regions, and the adoption of advanced technologies such as artificial intelligence (AI), internet of thing (IoT), and renewable energy in the agricultural sector has not been optimal. This research aims to develop an integrated smart farming system, including monitoring, controlling, and prediction features based on renewable energy to support national food security, especially for chili plants. The method used in the research is an experiment, starting from analysis, design, manufacture, and testing. The result of the research is a smart farming prototype that has been tested with experts, partners and farmers. The results of expert testing obtained that the monitoring feature, in this case the accuracy is 4.36 out of 5 for all sensors, as well as the controlling and prediction features have met technical, functional, and practical needs. The results of the usability evaluation using the system usability scale (SUS) method involving partners and farmers obtained an average SUS score of 73.125. This result is categorized as an excellent rating and can be given a grade B and the acceptance range is high. So, from this study it can be concluded that the smart farming prototype can be used by chili farmers.